Implementasi Kebijakan Command Center 112 di Surabaya - Leticia Nuzululita A; Anisa Sitta Ramadhani; Susi Hardjati (Jurnal Penelitian Administrasi Publik, 2020)
Command Center 112 is a public service innovation regarding disaster response in the city of Surabaya. This innovation is an emergency complaint report telephone service from the public that can be accessed 24 hours non-stop and toll-free. This service synergizes with Organisasi Perangkat Daerah (OPD) in one control room (Command Center Room). The purpose of this study is to find out how the implementation of the 112 Command Center policy in the city of Surabaya. The standard implementation theory used is the theory of George C. Edward III can be used as a reference to measure the success or failure of policy implementation, including (1) communication, (2) resources, (3) disposition and (4) bureaucratic structure according to journals (Putra & Tukiman, 2019). The research method used is descriptive qualitative method. Data collection techniques used are, interviews, observations, and documentation while the data analysis techniques in this study use an interactive analysis model developed by Miles and Huberman including data collection, data reduction, data display and conclusion drawing (Herdiansyah, 2010). The results of this study are based on the theory of George C. Edward III as a benchmark showing that the implementation of the Command Center 112 policy in the City of Surabaya has been well indicated by the Command Center Command Center 112 in the City of Surabaya held in one room or called the Command Center Room, in which there are various institutions or OPD to receive community reports and city conditions. However, there are still problems with people who often use this telephone service not in accordance with SOP (Standard Operating Procedure). In addition, re-socialization is needed so that people know and understand this service.